Using the SWAT model to identify erosion prone areas and to estimate soil loss and sediment transport in Mogi Guaçu River basin in Sao Paulo State, Brazil - dos Santos, Franciane Mendonça; de Souza Pelinson, Natália; de Oliveira, Rodrigo Proença; Di Lollo, José Augusto [UNESP] (Elsevier, 2023)
Water-driven erosion associated with the transport and deposition of sediments in watersheds may lead to contamination problems causing significant damage to land and infrastructure. The key factors that influence erosive processes are well known and include the precipitation rate, terrain topography, soil type, and vegetation cover. The soil and water assessment tool (SWAT) considers these factors and may be used to identify areas susceptible to soil erosion and to estimate soil loss and sediment transport and deposition. To corroborate this assumption, real data on rill erosion and sediment transport from the Mogi Guaçu River Basin in southeastern Brazil were used to validate SWAT estimates. The study shows that the model is able to identify soil-eroded areas and replicate the scale and variation patterns of sediment production, although not with great precision. Hence, it can successfully be used for prioritizing areas that require action and for evaluating alternative soil management and conservation practices to mitigate erosive processes.
Keywords: Erosion classification; Geohydrological modeling; Rural erosion; Soil degradation